Motion Control of Nonholonomic Wheeled Mobile Robot in a Structured Layout - Tang, Howe Hing; Mailah, Musa (Faculty of Mechanical Engineering, 2006)
This paper describes the incorporation of active force control (AFC) scheme into two different resolved motion acceleration control (RMAC) models, i.e. RMAC with proportional-plus-derivative (RMAC-PD) and RMAC with proportional-plus-integralplus- derivative (RMAC-PID). The two newly formulated control models are subsequently implemented as the proposed motion controllers for the nonholonomic wheeled mobile robot (WMR). By embedding AFC into both the RMAC schemes, the performance of the robotic system was studied in which the WMR was required to track a collision-free trajectory in a structured layout that has been prescribed by a trajectory planner. The effectiveness of both the controllers were then experimented and compared to determine the accuracy and trackability of the WMR. The WMR was also subjected to disturbances for the testing of the system robustness. With appropriately computed inertia matrix and finely tuned RMAC control parameters, the WMR was found to be very robust and effective in trajectory tracking task in spite of the complexity of the operating and loading conditions.